Alternative sanctions for drug users: fruitless efforts or miracle solution? - De Wree, Eveline (Crime, law and social change, 2009)
In most Western European countries, including Belgium, judicial alternative sanctions are increasingly being used for drug users. Because no study into the effectiveness of Belgian judicial alternatives for drug users has yet been carried out, this became the objective of the current research. The design of this study comprises a pre and post measurement of the criminal activity, drug use and situation in different spheres of life of 565 drug-dependent offenders. Two conclusions can be drawn. First, after an alternative sanction or measure is imposed, there is a reduction in the criminal activity of the offender. Second, this crime reduction goes hand in hand with a progress in several relevant life spheres.